The prognostic value of preprocedural high-sensitivity troponin T in patients with severe aortic stenosis undergoing valve replacement: a gender analysis. (25th November 2020) - Barbieri, F; Senoner, T; Adukauskaite, A; Lambert, T; Zweiker, D; Rainer, P; Schmidt, A; Feuchtner, G; Steinwender, C; Hoppe, U; Hintringer, F; Bauer, A; et al.
Abstract: Introduction: Recent studies have demonstrated the predictive value of preprocedural cardiac biomarkers, such as N-terminal pro brain natriuretic peptide (NT-proBNP) and high-sensitivity troponin T (hsTnT), in patients with severe aortic valve stenosis undergoing valve replacement. Nonetheless, it remains still unclear whether hsTnT may be influenced by gender-specific differences. Purpose: The aim of this subanalysis was to evaluate sex-related differences of preprocedural hsTnT in predicting postoperative long-term survival in a large cohort undergoing either surgical or transcatheter aortic valve replacement. Methods: The TASS-2 group, a consortium of four university hospital centers, analysed 3595 consecutively enrolled patients admitted for valve implantation because of severe aortic stenosis between 2007 and 2017. Results: The study cohort consisted of 1728 (48.1%) female and 1867 (51.9%) male patients. During a median follow-up of 2.9 years, cardiovascular mortality was found in 556 (15.5%) patients, amongst whom were 292 (16.9%) women and 264 (14.1%) men. All-cause mortality was detected in 919 (25.6%) patients dividing into 462 (26.7%) women and 457 (24.5%) men. Preprocedural hsTnT was significantly higher (p<0.001) in male (19 ng/l, 11.8–34.0) than in female (16 ng/l, 10.0–30.0) patients. In contrary, NT-proBNP was lower (p=0.002) in male (1286 ng/l, 444.5–3225.5) than female (1407 ng/l, 604.5–3217.5) patients. For the univariate analysis of survival, hsTnT was categorized by using predefined subgroups (<5 ng/l; 5–13.99 ng/l; 14–50 ng/l; >50 ng/l). Cardiovascular and all-cause mortality were significantly increased with higher hsTnT plasma levels in women (p<0.001) as well as in men (<0.001). In two separate multivariate cox regression models, one for either gender - adjusting for STS risk score, NT-proBNP plasma levels, degree of left ventricular systolic dysfunction, atrial fibrillation, age, renal function, chronic obstructive pneumonic disease, arterial hypertension, diabetes mellitus, concomitant significant coronary artery disease and type of procedure – pre-procedural hsTnT was a strong independent predictor for postoperative cardiovascular mortality with an hazard ratio [HR] of 3.34, 95% confidence interval [CI] 1.03–10.80, P=0.044 for mildly to moderately elevated hsTnT (14–50 ng/l) and an HR of 3.98, CI 1.19–13.30, P=0.025 for severely elevated hsTnT (>50 ng/l) in women, whereas an hazard ratio [HR] 4.09, 95% confidence interval [CI] 0.55–29.99, P=0.166 for mildly to moderately elevated hsTnT (14–50 ng/l) and an HR 7.48, CI 0.99–56.12, P=0.050 for severely elevated hsTnT (>50 ng/l) in men was yielded. Conclusion: Long-term postoperative survival in patients with severe AS admitted for valve implantation was independently predicted by hsTnT, irrespective of gender. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Tiroler Wissenschaftsförderung (Innsbruck, Austria)